SKRINING THALASSEMIA PADA SUKU ANAK DALAM DI PROVINSI JAMBI - Sotianingsih, Sotianingsih; AS, Charles; M, Ita (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Background: thalassemia mutations are very diverse and can be ethnic-specific. Prevention is done through screening of carrier traits, counseling and prenatal diagnosis; which will be optimal when accompanied by carrier frequency data and spectral data type of mutation Purpose of research: to determine the frequency of carrier of thalassemia character of suku anak dalam in Jambi Province Methods of research: descriptive, as many as 35 respondents of suku anak dalam in of Sei Ulak village. Performed the making of blood smear and venous blood sampling. Blood smear were given Wright-Giemsa staining. A complete blood examination was performed with a Sysmex Xs-800i hematology analyzer. Hb analysis using Capillary electrophoresis model Minicap Flex-piercing from Sebia. DNA analysis was performed by SEA, Fil and Thai Delight, Delete 3.7 and 4.2kb, and HbCS and Hb Adana point mutations Results: Haemoglobin <normal at age 5 - <12 years 2.86% mild and moderate 2.86%, age> 15 years, women 2.86% mild, age> 15 years, men 5.71% mild, peripheral blood 8.57% found microcytic hypochromic cells 5.71% of the mixed HbA averages 97.1, 97.0 (33.3%) while HbA1 2.8, 3.0 (33.3%). HbF is present in 1 sample. DNA analysis not found mutation Conclusions and suggestions: Conclusions: In Suku Anak Dalam we found mild anemia 11.42% and moderate anemia 2.86%. Smear of blood found 8.57% hypochrome microscopic cells and 5.71% mixture. HbA 97.0 (33.3%), HbA2 highest 3.0 (33.3%). HbF 1 (2.86%). There is 1 (2.86.7%) suspect carrier of thalassemia a and there is 1 (2.8%) suspect variant Hb. This result excludes the possibility of carrying thalassemia trait a mild 3 respondents (8.57%). Suggestion: Advanced molecular examination of DNA sequencing Keywords: Suku Anak Dalam, Haemoglobin, Hb Analysis, Thalassemia a, Thalassemia